Online Learning Using Google Classroom for Biology Education Students During Covid-19 Outbreak - Jayanti Syahfitri; Meti Herlina (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
Several online learning media have been implemented at one of universities in Bengkulu City, Indonesia, one of which was Google Classroom. This study aims to determine how the motivation and learning outcomes of Biology Education students after being taught using Google Classroom media. This research used a pre-experimental design one group pre-test-posttest. The sample involved was one class with a total of 26 biology education students. Student motivation was measured using a questionnaire instrument, while for learning outcomes using a test instrument. The data obtained were first analyzed for normality test through the Kolmogorov-Smirnov test. Based on the results of the normality test, it can be seen that the student motivation data shows that the data is normally distributed (with sig 0.194 ˃ 0.05), so it is followed by hypothesis testing through the Paired t-Test. The t-test results show that there is a significant difference in student motivation before and after being taught through Google Classroom with sig 0.000 0.05. On the other hand, the learning outcomes data, the normality test shows that the data is not normally distributed (with a sig value nilai 0.05), so the hypothesis is tested through non-parametric tests, namely the Wilcoxon test. The Wilcoxon test also shows that there is a significant difference in student learning outcomes before and after being taught through Google Classroom with sig 0.000 0.05. Suggestions for further researchers can analyze how the differences and effectiveness of several other e-learning media in learning biology in universities are. In addition, curriculum developers need to pay attention to how to analyze or evaluate online learning.